For as defined above, find the value of .
For fun purpose one may wish to solve it without using the standard known formula.
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Find 1 + ( 1 + 2 ) + ( 1 + 2 + 3 ) + ⋯ + ( 1 + 2 + 3 + ⋯ + n ) We write the above finite sum in terms of double dependent sum as
Solution 1 (Using standard formula) F ( n ) = k = 1 ∑ n m = 1 ∑ k m = 2 1 k = 1 ∑ n k ( k + 1 ) = 2 1 ( 6 n ( n + 1 ) ( 2 n + 1 ) + 2 n ( n + 1 ) ) = 3 n + 2 T n
Solution 2 (Without using standard formula)
Now suppose we try to evaluate the sum without using the standard formula. To do so we note that for k ≤ n n 1 + 1 + ⋯ + 1 + n − 1 2 + 2 + ⋯ + 2 + ⋯ + n − 9 1 0 + 1 0 + ⋯ + 1 0 + ⋯ n − m + 1 m + m + ⋯ + m So F ( n ) = k = 1 ∑ n m = 1 ∑ k m = k = 1 ∑ n m = 1 ∑ n − k + 1 k = k = 1 ∑ n m = 1 ∑ n k − k = 1 ∑ n m = 1 ∑ k ( m + 1 ) + 2 k = 1 ∑ n k F ( n ) = k = 1 ∑ n + 2 k = 1 ∑ n k − 2 k = 1 ∑ n m = 1 ∑ k m ⇒ 3 F ( n ) = ( n + 2 ) k = 1 ∑ n k ⇒ F ( n ) = 3 ( n + 2 ) k = 1 ∑ n k = 3 n + 2 k = 1 ∑ n ( 2 k + ( n − k + 1 ) ) = 6 n + 2 k = 1 ∑ n ( n + 1 ) = 6 n ( n + 1 ) ( n + 2 ) = ( 3 n + 2 )
Solution 3 (Using combinatorial identities) k = 1 ∑ n m = 1 ∑ m m = k = 1 ∑ n T k = k = 1 ∑ n ( 2 k + 1 ) = 4 1 ( 3 2 n + 2 ) + ( 2 n + 1 ) = s i m p l i f y ( 3 n + 2 ) Solution 4 : One can try up with ordinary generating function.